Diversity, bioactivity, and phytochemistry of endophytic fungi in various organs of nipa palm (Nypa fruticans) mangrove - SAKINAH SALMAN AHMAD NASUTION; ELFITA ELFITA; HARY WIDJAJANTI; FERLINAHAYATI FERLINAHAYATI (Society for Indonesian Biodiversity, 2024)
Abstract. Nasution SSA, Elfita, Widjajanti H, Ferlinahayati. 2024. Diversity, bioactivity, and phytochemistry of endophytic fungi in various organs of nipa palm (Nypa fruticans) mangrove. Biodiversitas 25: 3928-3942. Nipa palm (Nypa fruticans Wurmb), a traditional medicinal mangrove species, grows along the coastal areas of South Sumatra. This study explores the diversity of endophytic fungi isolated from the stem, frond, and mesocarp of N. fruticans. A total of eighteen fungal isolates were identified and tested for antioxidant and antibacterial activities using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and the disk diffusion method. Phytochemical profiles of these isolates were analyzed through thin layer chromatography (TLC) and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Among the isolates, Aspergillus niger (NfBa5, NfP7, and NfBu4), present in all organs, showed consistent antioxidant and antibacterial activities with similar major compounds across these isolates. Other endophytic fungi demonstrated significantly higher antioxidant and antibacterial activities compared to the host plant, highlighting their potential as promising sources of bioactive compounds. Despite some shared compound patterns, the fungal profiles differed from those of N. fruticans, underscoring the unique bioactive potential of endophytes. This study emphasizes the diversity of endophytic fungi in N. fruticans and reveals significant differences in their biological activities and phytochemical profiles compared to the host. These findings provide foundational insights for developing medicinal compounds from N. fruticans endophytic fungi for future pharmaceutical applications.